Arabic-English dictionary of Qur'anic usage - Badawi, El-Said M. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2008)
The Qur'an is the living source of all Islamic teaching, and is of singular importance to those interested in Islam and the study of religions. Despite this, there exists a long-felt lack of research tools for English first-language speakers who wish to access the Qur'an in the original Arabic. The Dictionary of Qur'anic Usage is the first comprehensive, fully-researched and contextualised Arabic-English dictionary of Qur'anic usage, compiled in accordance with modern lexicographical methods by scholars who have a lifelong immersion in Qur'anic Studies. Based on Classical Arabic dictionaries and Qur'an commentaries, this work also emphasises the role of context in determining the meaning-scatter of each vocabulary item. Illustrative examples from Qur'anic verses are provided in support of the definitions given for each context in which a particular word occurs, with cross-references to other usages. Frequently occurring grammatical particles are likewise thoroughly explained, insofar as they are used in conveying various nuances of meaning in the text.